The Helicobacter pylori Vacuolating Toxin Inhibits T Cell Activation by Two Independent Mechanisms - Boncristiano, Marianna (The Rockefeller University Press, 2003)
Helicobacter pylori toxin, VacA, damages the gastric epithelium by erosion and loosening of tight junctions. Here we report that VacA also interferes with T cell activation by two different mechanisms. Formation of anion-specific channels by VacA prevents calcium influx from the extracellular milieu. The transcription factor NF-AT thus fails to translocate to the nucleus and activate key cytokine genes. A second, channel-independent mechanism involves activation of intracellular signaling through the mitogen-activated protein kinases MKK3/6 and p38 and the Rac-specific nucleotide exchange factor, Vav. As a consequence of aberrant Rac activation, disordered actin polymerization is stimulated. The resulting defects in T cell activation may help H. pylori to prevent an effective immune response leading to chronic colonization of its gastric niche.